East Bay for Everyone. - East Bay for Everyone (Organization) (Oakland, California : East Bay for Everyone, 2017)
"East Bay for Everyone (formerly East Bay Forward) is a network of people fighting for the future of housing, transit, tenant rights, and long-term planning in the East Bay. We believe in more housing, more renter protections, better public transit, and better infrastructure."
Preserved in: Collaborative Architecture, Urbanism, and Sustainability Web Archive (CAUSEWAY).
Identification of the resource based on contents viewed on March 15, 2018; title from home page.
Keywords: East Bay for Everyone (Organization); Housing -- California -- East Bay; Transportation -- California -- East Bay; City planning -- California -- East Bay; Apartment dwellers -- California -- East Bay; East Bay (Calif.); Apartment dwellers; City planning; Housing; Transportation; California -- East Bay